Quality and Release Profile of Captopril from Mucoadhesive Gastroretentive Tablet by Using Matrix Sodium Carboxymethyl Cellulose and Carbopol 934P - Isriany Ismail; M. Asrah Hidayah Usman; Nur Ida (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2020)
Captopril have good absorption in gastric pH and ionized on intestinal pH. It is necessary to keep the drug in the form of molecules in the area of the absoption. The mucoadhesive gastroretensive drug delivery system provides the possibility of controlled release in stomach in a certain amount of time. Research has been conducted to assess the quality and profile of captopril release in of a mucoadhesive gastroretensive tablet. Mucoadhesive tablets (MK) were made in 5 formulas by wet granulation method using carbopol 934P and sodium carboxymethyl cellulose as matrix with ratio 10: 0 (MK1), 0: 10 (MK2), 5: 5 (MK3), 7: 3 (MK4), and 3: 7 (MK5). The parameters which was evaluate were characteristics of granules and tablets and kinetics model of captopril release from tablets in 0,01 N HCl medium. Mucoadhesive tablets had different characteristics for each formula. Mucoadhesive tablets that had good quality and release profile were shown by MK4 and MK5 formula. They had controlled drug release profiles accorded to the Korsmeyer-Peppas and Higuchi kinetics models, respectively.